(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper present the design of a field-programmable gate array (FPGA)-based traffic light controller (TLC) with the internet of things (IoT). This approach controls the traffics problem since traffic congestion is a phenomenon that significantly impacted Malaysia’s transportation system, especially for emergency vehicles. This problem has affected emergency transportation such as ambulance to make way at the traffic light intersection, which is always busy. This system was designed using FPGA with an IoT platform. Its give priority to emergency vehicles, especially ambulances at the traffic lights intersections. The two objectives for this project are to design and implement the TLC using FPGA at intersection roads and to notify the current traffic condition more systematically by implementing an IoT part. The IoT application is connected to the emergency vehicles driver, informing them of the current traffics light state. The prototype of this project was simulated using Cyclone V and implemented on a DE-10 Nano board as hardware. As for the IoT part, this project uses an ESP8266 Wi-Fi module. The TLC implementation in this project successfully detected an emergency vehicle and notified the driver of the TLC condition.